Land-use classification and mapping using landsat 8 imagery for GIS database in Langkawi Island - Ahmad, Zuhairi; Azman, Nur Syahira Azlyn; Md. Rosli, Nur Suhaila; , (Kulliyyah of Science, 2019)
Land use is a physical property of the land which gives information regarding the function of the land resources. Furthermore, a land use map functions by relaying the information of land use within the area visually. Langkawi Island being one of the main attractions in Malaysia has undergone rapid development due to tourism industry. Therefore, this paper studies the land use changes in the Langkawi Island over the period of 12 years. Land use maps were derived by analyzing temporally available satellite imageries of the area. Subsequent Landsat imageries of the year 2006, 2012 and 2018 were processed in ENVI using Normalize Difference Built-Up Index (NDBI) and supervised classification. The land use classes obtained were categorized according to the SWAT land use classification namely FRSE, AGRL, URBN, UCOM, UIDU, and UTRN. The analysis the land use maps provided the statistical comparison for the changes in the land use classes around the Langkawi Island. The changes in the area has increased especially in the urban categories. This research will provide an overview for the stakeholder to analyze the current land use of the Langkawi Island and develop future land use planning. Moreover, the map can be used for a functional land use input in the SWAT modelling and provide a temporal GIS database on the land use of Langkawi Island.